2021
DOI: 10.1029/2020wr029434
|View full text |Cite
|
Sign up to set email alerts
|

Potential Drought Mitigation Through Microbial Induced Calcite Precipitation‐MICP

Abstract: Extreme drought events occur more frequently due to climate change. Soil water loss through evaporation is therefore significantly intensified. This study introduces an environment‐friendly and sustainable bio‐mediated technique, known as microbially induced calcite precipitation (MICP), for water evaporation suppression in clayey soils. Through lab‐scale evaporation tests, we investigate the effects of cementation solution concentration (0.5, 1.0, and 1.5 mol/L) and MICP treatment procedure (one‐phase and two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 67 publications
(82 reference statements)
2
12
0
Order By: Relevance
“…This crust exhibits a stable porous structure (see Figure 12m) and functions as a protective layer on the soil surface. In arid climates, the CaCO 3 crust reduces water vapor diffusion from the soil to the atmosphere, thus decreasing the soil water evaporation rate and suppressing cracking (Liu, Tang, et al., 2021). The surface crust can mitigate soil erosion in regions with severe rainfall by protecting the underlying soil from runoff and reducing rainwater infiltration, thus preventing internal soil erosion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This crust exhibits a stable porous structure (see Figure 12m) and functions as a protective layer on the soil surface. In arid climates, the CaCO 3 crust reduces water vapor diffusion from the soil to the atmosphere, thus decreasing the soil water evaporation rate and suppressing cracking (Liu, Tang, et al., 2021). The surface crust can mitigate soil erosion in regions with severe rainfall by protecting the underlying soil from runoff and reducing rainwater infiltration, thus preventing internal soil erosion.…”
Section: Discussionmentioning
confidence: 99%
“…MICP has also shown feasibility in erosion control and dust suppression (Liu, Xie, et al., 2021; Meyer et al., 2011; Salifu et al., 2016). Furthermore, recent studies have shown the benefits of MICP in enhancing soil resistance to desiccation cracking (Liu et al., 2020) and mitigating the adverse impacts of drought on soils by suppressing the soil water evaporation (Liu, Tang, et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It contains 2% sand, 76% silt, 22% clay, and has a liquid limit of 37% and a plastic limit of 20%. Previous study indicates that the dominant clay minerals are illite and illite‐smectite (Liu et al., 2021). And the detailed physical characteristics of the soil can be found in previous literatures (e.g., Liu, Pollard, et al., 2013; Liu, Shi, et al., 2013)…”
Section: Laboratory Model Testmentioning
confidence: 94%
“…It contains 2% sand, 76% silt, 22% clay, and has a liquid limit of 37% and a plastic limit of 20%. Previous study indicates that the dominant clay minerals are illite and illite-smectite (Liu et al, 2021). And the detailed physical characteristics of the soil can be found in previous literatures (e.g., Liu, Pollard, et al, 2013; Water table tubes are installed on the inner side of the model box every 10 cm, from 5 to 55 cm, in order to investigate the variation of water level and water pressure.…”
Section: The Test Equipment and Soilmentioning
confidence: 99%
“…Calcium carbonate affects many soil physical and chemical properties. These include aggregation of primary particles, soil water retention, pH, micronutrient availability, stabilization of soil organic C, and NH 3 volatilization (Bronick & Lal, 2005; Liu et al., 2021; Loeppert & Suarez, 1996; Rowley et al., 2018; Ryan et al., 1981). However, these effects depend less on the total concentration of soil carbonate and more on the reactivity of that carbonate which is controlled by particle size and surface area (Estefan et al., 2013).…”
Section: Introductionmentioning
confidence: 99%